Perception regarding humanizing healthcare among the national healthcare service patients in Évora area - Portugal - Batanete, Ermelinda do Carmo Valente Caldeira; Casas-Nova, Maria Vitória Glórias Almeida (Revista de Enfermagem UFPE on line, 2011)
ABSTRACT Objective: to ascertain the perception regarding humanizing healthcare among the National Healthcare Service (NHS) patients in the area of Évora - Portugal. Method: this is a descriptive study, exploratory, with a quantitative approach using a random sampling starting from the guiding question: What is the NHS patients’ perception on humanizing the care provided by the healthcare services? Data were collected with an informed consent questionnaire, administered between September and October 2010 to 62 individuals who were patients in the NHS, according to the approval of the Ethic Committee on Research Involving Human Beings, with the 203/2008 legal opinion. Results: concerning humanizing health care, the respondents of this study outlined as particularly important aspects the following: being attended by gracious professionals who facilitate the dialogue and provide quality care in a short period of time. The value placed on being able to select one’s doctor and nurse is explained by aspects that patients find important such as availability, confidentiality, competence as well as the continuity of care and trust for the health professionals. Conclusion: the results highlight the following aspects: communication; attitudes and competence of the health professionals; accessibility and exercise of autonomy. Descriptores: humanizing; health care; health systems; consumer satisfaction; perception RESUMO Objetivo: conhecer a percepção dos usuários do Serviço Nacional de Saúde (SNS) do conselho de Évora - Portugal acerca da humanização dos cuidados. Método: estudo descritivo, exploratório, de abordagem quantitativa com uma amostra acidental, a partir da questão norteadora: Como é que os usuários do SNS percepcionam a humanização dos cuidados prestados nos serviços de saúde? A colheita de dados foi realizada através de um questionário com consentimento livre e esclarecido, aplicado entre setembro e outubro de 2010 a 62 sujeitos usuários do SNS, conforme aprovação do Comité de Ética em Pesquisa Envolvendo Seres Humanos. Resultados: acerca da humanização dos cuidados de saúde os informantes deste estudo evidenciaram como aspectos particularmente importantes, um atendimento por profissionais simpáticos, que facilitem o diálogo e prestem cuidados de qualidade num curto espaço de tempo. A importância da escolha do médico e do enfermeiro de familia, pelos usuários do SNS, é justificada pela disponibilidade, a confidencialidade, a competência, assim como a continuidade de cuidados e a confiança nos profissionais de saúde. Conclusão: os resultados remetem-nos para um acentuado destaque dos seguintes aspectos: a comunicação; atitudes e competência dos profisionais de saúde; acessibilidade e exercício da autonomia. Descritores: humanização; cuidados; sistemas de saúde; satisfação dos consumidores; percepção. RESUMEN Objetivo: conocer la opinión de los usuarios del servicio nacional de Saúde (SNS) del consejo de Évora- Portugal sobre la humanizácion de los cuidados. Método: estudio descriptivo, exploratório, de abordage cuantitativa con una muestra aleatoria, basando-se en la pregunta norteadora: ¿Cómo los usuarios del SNS percepcionan la humanizácion de los cuidados prestados por los servicios de salud? La cosecha de datos fue hecha utilizando un cuestionario con consentimiento libre y clarificado, aplicado entre septiembre y octubre de 2010 a 62 usuarios del SNS, con aprobación del Comité de Ética en la Investigación en Seres Humanos, con el dictamen legal 203/2008. Resultados: referente a la humanizácion de los cuidados de salud, los informadores de este estudio habían evidenciado particularmente como aspectos importantes, la atención de profesionales agradables que facilitan el diálogo y dan cuidados de calidad en poco tiempo. La seleccion del doctor y de la enfermera es justificada por la importancia que asume para los usuarios la disponibilidad, la confidencialidad, la competencia, así como la continuidad de cuidados y la confianza en los profesionales de salud. Conclusión: los resultados nos apuntan para la importancia de los aspectos siguientes: la comunicación; actitudes y capacidad de los profisionales de la salud; accesibilidad y ejercicio de la autonomía. Descriptores: humanizácion; cuidados; sistemas de salud; satisfacción de los consumidores; percepción.